Philanthropy: A Customary Practice to Meet Donor Expectations Lesson from Islamic NPOs in Indonesia - Muji Astuti Rejosumarto; Mehmet Bulut (European Scientific Journal, ESJ, 2024)
Philanthropy is a form of altruism that comprises private initiatives that enhance the public good. Throughout history, benevolence or voluntary contributions have appeared in numerous shapes and objectives, representing the economic and political framework of the time and various motivations. Non-profit organizations (NPOs) in Indonesia have undergone tremendous transformations, evolving to be more modern and professional. They determine market segments, manage donor networks, formulate fundraising strategies, and construct appropriate, impactful, and beneficial programs with the organization's system and human capital. Aside from that, Islamic NPOs have become more strategic and able to preserve a clear vision and mission. They have also established organizational structures, appointed qualified leaders, and designed long-term, medium-term, and short-term activity plans and budgets. Moreover, they have appointed program supervisors and assessed the effectiveness and efficiency of their plans. This research aims to investigate the broad issues confronting Islamic charity in Indonesia as it evolves towards a strategic institution. This study adopted qualitative methodologies to discover comprehensive explanations for the occurrences studied. In-depth semi-structured interviews with an array of practitioners and academics were employed to gather data. This study found that a great deal of effort is required to improve the capabilities of Islamic NPOs in terms of good governance, system strengthening, cultural internalization, public openness, and accountability. Such aspects are important for establishing effective intermediary organizations that meet donor expectations. Therefore, Islamic NPOs must accelerate capacity building by enhancing each aspect of the organization to sustainably impact its beneficiaries positively.